The relationship between Emotional Intelligence and Occupational Stress among Nurses of Alzahra Hospital in Isfahan - marziye kheirmand; farzad kheirmand; Ayoub Pazhouhan (Tehran University of Medical Sciences, 2016)
Background: Nursing is considered as one of the most stressful occupation which influences their quality of work and life. The inevitable fact of occupational stress and low emotional intelligence management leads to negative effect on the nurses' performance. The study aimed at determining the relationship between emotional intelligence and occupational stress among the nurses of alzahra hospital in Isfahan. Materials and Methods: This study was an applied and descriptive survey. The study population consisted of 960 nurses of alzahra hospital in Isfahan. Sample size calculated 247 using Cochran formula. Sampling method was stratified random sampling. Data gathering was used by two questionnaires including emotional intelligence (sybershring) with 0.85 reliability coefficient and Health and Safety Institution of England (HSE) questionnaire with 0.84 reliability coefficients. Data analysis performed by SPSS software using independent t-test and Pierson Correlation Coefficient tests. Results: Findings revealed that the stress level and its measuring scales such as expectations, control, management support, colleague's support and role ranked more and the interrelation scale  ranked less than average among nurses. Emotional intelligence level of nurses and scales such as self-awareness and self-regulation ranked average  and empathy, self-motivation and social skills ranked less than average. Therefore, there was a significant relation between the emotional intelligence level and nurseschr('39') stress in p<0.05. With increasing the emotional intelligence level, the occupational stress in nurses decreased. Conclusions: Having emotional intelligence skills can result in experiencing stress less and improving nursing performance; and better service quality among patients.  Hence, hospital's managers should be adopting proper policies with respect to the emotional intelligence.